Phycoremediation and valorization of synthetic dairy wastewater using microalgal consortia of Chlorella variabilis and Scenedesmus obliquus. Issue 20 (6th September 2021) - Gatamaneni Loganathan, Bhalamurugan; Orsat, Valerie; Lefsrud, Mark
ABSTRACT: Microalgae are known to grow on wastewater utilizing their available nutrients. The residual algal biomass thus obtained could be used for producing value-added products thereby making it an economically viable and sustainable option for the dairy industry. The present study evaluates the ability of the microalgal consortia composed of Chlorella variabilis and Scenedesmus obliquus to treat and valorize diluted synthetic dairy wastewater under controlled laboratory conditions. The effect of time, inoculum concentration and light intensity on five responses, namely phosphate removal, ammoniacal nitrogen removal, COD removal, biomass productivity and lutein content, are studied by response surface methodology utilizing central composite design. The quadratic models are found to be suitable for phosphate removal, ammoniacal nitrogen removal, COD removal and biomass productivity. At optimized experimental conditions, the microalgal consortia exhibited phosphate removal of 70.19%, ammoniacal nitrogen removal of 86.22%, COD removal of 54.72%, biomass productivity of 29.13 mg/L/day and lutein content of 12.59 mg/g respectively. This study is of high importance as the lutein content exhibited by the microalgal consortia is higher when compared to other microalgal species and could be considered in the future as a commercial source of lutein. GRAPHICAL ABSTRACT: UF0001